Evaluation of the substance of consumptive murabahah: Maqāṣid perspectives, regulation, and sharia accounting - Nurbaidah, Siti Umi; Hidayah, Nur; Muhajirin, Muhajirin (Journal of Contemporary Accounting, 2025)
This paper aims to evaluate the application of the Murabaha contract in consumer financing within Indonesian Islamic banks based on the substantive principles of sharia and the maqāṣid framework of Ibn ‘Āshūr. The study adopts a normative-qualitative and descriptive-comparative method analyzing PSAK 102/402, DSN-MUI fatwas, and real practices in Bank Syariah Indonesia (BSI). Data were collected through document review and interviews with practitioners. The findings reveal that current Murabaha practices emphasize administrative compliance over the substantive nature of sale transactions, with fixed margins often benchmarked to interest rates. This raises the potential for hidden riba and contradicts maqāṣid values such as ḥifẓ al-māl (wealth protection), al-‘adl (justice), and al-ṣidq (truthfulness). The paper proposes a margin determination model based on 'iwāḍ (legitimate compensation for risk and effort) and recommends reformulating financial reports aligned with maqāṣid principles. This study contributes to both conceptual and technical reform in Islamic finance, with significant implications for regulation and Islamic accounting education